Antinociceptive and anti-ulcerogenic effect of hydroethanolic stem bark extract of Ricinodendron heudelotii (Baill.) Pierre ex. Heckel (Euphorbiaceae): Involvement of the opioidergic pathway and attenuation of oxidative stress - Isaac Tabiri Henneh; Wisdom Ahlidja; Ernest Amponsah Asiamah; Denzel Opoku-Kwabi; Henry Mensah Korsah; Fynn Malcom; Stephen Mensah Arhin; Michael Buenor Adinortey; Francis Ackah Armah (Journal of Traditional and Complementary Medicine)
Background and aim: Approximately 80% of the population in developing countries is affected by gastric ulcers. Gastric ulcers are associated with pain, and there is an urgent need for drugs that can manage both conditions. Ricinodendron heudelotii (Baill.) Pierre ex. Heckel has long been used in managing gastric ulcers and pain in African Traditional Medicine. In the present study, the antinociceptive and anti-ulcer activity of Ricinodendron heudelotii hydroethanolic stem bark extract (RHE) was evaluated. Experimental procedure: The antinociceptive effect of RHE was tested in ICR mice using the hot plate test, the glutamate-induced nociceptive test, and the formalin test. Gastric ulcers were induced in healthy male adult albino rats in acidified alcohol-induced ulcer (AAIU) and indomethacin-induced ulcer (IIU) models. After ulcer induction, the rats were treated with either RHE (30, 100, or 300 mg/kg, p.o.) or 10 mg/kg omeprazole. The stomachs of the sacrificed animals were removed for further analysis. Results and conclusion: RHE (30, 100, and 300 mg/kg) exhibited an anti-nociceptive effect in the hot plate, formalin and glutamate tests. The opioid receptor antagonist, naloxone, reversed the analgesic effect, indicating that the extract may be acting via the opioidergic pathway. But compared to the model group in both AAIU and IIU, oral administration of RHE decreased ulcer index, raised gastric pH levels, increased tissue levels of total antioxidant capacity, catalase, total thiols, and glutathione, and kept gastric histoarchitecture intact. RHE exhibited anti-nociceptive effects, possibly via the opioidergic pathway and anti-ulcer activity via reduction of oxidative stress.